2016
DOI: 10.1109/tcomm.2016.2537328
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Performance Evaluation and Optimization of UW-OFDM

Abstract: Abstract-Unique-word (UW) OFDM is a new OFDM variant that offers several advantages over cyclic prefix OFDM, such as better bit-error-rate (BER) performance in frequency selective channels and much lower out-of-band radiation. However, all results with respect to the BER performance are based on MonteCarlo simulations only, and offer little insight in the behaviour of the system performance as function of its parameters. In this paper, we theoretically analyse the performance of the UW-OFDM system for both a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Because although the constraint (5) guarantees to have full diversity at very high SNRs, the true diversity gain at moderate SNR levels will depend on the eigenvalues of the matrix G H B H H H HBG, where H is the diagonal matrix with as diagonal elements the frequency response of the channel [5].…”
Section: Simulation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because although the constraint (5) guarantees to have full diversity at very high SNRs, the true diversity gain at moderate SNR levels will depend on the eigenvalues of the matrix G H B H H H HBG, where H is the diagonal matrix with as diagonal elements the frequency response of the channel [5].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In practical systems, often the transmitted energy per data symbol is normalized, leading to trace G H G = N d . Further, in [1], [5], it is shown that the condition…”
Section: B Design Of the Generator Matrixmentioning
confidence: 97%
See 3 more Smart Citations